THE IMPORTANCE OF IMPROVING THE PEDAGOGICAL ABILITIES OF TEACHERS IN THE EDUCATIONAL PROCESS IN AN INTEGRATIVE DIRECTION - Xolmuminova Dilfuza (Web of Journals Publishing, 2024)
Higher education institutions are considered as a new social need to improve the pedagogical abilities of teachers of the preschool educational direction in an integrative direction, to further improve the quality of Higher Education. This article discussed the importance of improving the pedagogical abilities of teachers in the educational process in an integrative direction.
Keywords: education, demand of the times, modern approaches, professional activity, specialization, training of specialists, pedagogical skills, new social needs, reforms, integrative approach.